Understanding Gender Dynamics in Teacher Educators' Computer Self-Efficacy - Bala, Rajni (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This study examines computer self-efficacy among teacher educators, defined as the confidence in one's ability to effectively utilize computer technology for educational purposes. The main aim is to investigate gender differences in self-efficacy across three competency levels: basic, intermediate, and advanced. Utilizing a quantitative research approach, a self-constructed questionnaire containing 35 items was distributed to a purposive sample of 100 teacher educators, which included 61 female and 39 male participants. T-tests were employed to analyze the differences in self-efficacy scores between genders. The findings indicate no significant difference in self-efficacy at the basic competency level (t = 0.8391). In contrast, female educators displayed significantly higher self-efficacy scores in intermediate (t = 4.1417) and advanced competencies (t = 4.2159). Furthermore, female educators achieved an average score of 142.62 on the overall computer self-efficacy scale, notably exceeding the average score of 117.28 for male educators (t = 5.0717). Thus, the study reveals important gender dynamics in computer self-efficacy among teacher educators. It indicates that female educators tend to have greater confidence in their computer skills as they advance in competency levels. This highlights the need to address gender disparities in professional development initiatives and suggests that further research should explore the underlying factors that influence self-efficacy in technology use among educators.